Changes of legal forms at professional football ventures - Nagy, Imre; Bácsné Bába, Éva (Acta Agraria Debreceniensis, 2014)
Since the ’90s professional football has been going through an unprecedented economic growth. The football ventures are becoming more and more middle-sized companies. In football there are organizational changes, which are reflected in changes of legal forms of professional football clubs, and in using of modern controlling, planning, risk and financial management. In this paper we primarily wish to show the specificities of legal forms in German professional football, because we believe the German model is the best example for the future development of football around the world, and we believe this would be most advantageous towards our future development at home.